2017
DOI: 10.1016/j.neurobiolaging.2017.01.025
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional comparison of ethanol-related cytokine expression in the hippocampus of young and aged Fischer 344 rats

Abstract: Our work in Sprague Dawley rats has shown rapid alterations in neuroimmune gene expression (RANGE) in the hippocampus and paraventricular nucleus of the hypothalamus (PVN). These manifest as increased Interleukin (IL)-6 and IκBα, and suppressed IL-1β and Tumor necrosis factor alpha (TNFα) during acute ethanol intoxication. The present studies tested these effects across the lifespan (young adulthood at 2–3 months; senescence at 18 and 24 months), as well as across strain (Fischer 344) and sex. The hippocampus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 49 publications
2
20
1
Order By: Relevance
“…7 Follow-up work replicated this effect and extended it to other brain regions (i.e. amygdala), repeated ethanol exposures, and other rat strains, [8][9][10] suggesting that ethanol-induced IL-6 expression is highly reproducible and much more widespread in the CNS than originally thought.…”
Section: Impact Statementmentioning
confidence: 73%
See 2 more Smart Citations
“…7 Follow-up work replicated this effect and extended it to other brain regions (i.e. amygdala), repeated ethanol exposures, and other rat strains, [8][9][10] suggesting that ethanol-induced IL-6 expression is highly reproducible and much more widespread in the CNS than originally thought.…”
Section: Impact Statementmentioning
confidence: 73%
“…We expected that cues associated with ethanol would elicit a conditioned increase in IL-6 and IjBa two neuroimmune genes known to increase during ethanol intoxication. 7,8,10 As an added benefit, this procedure allowed us to examine behavioral conditioning (i.e. avoidance of the taste CS) in tandem with the potential neuroimmune adaptations.…”
Section: Impact Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…While these initial foundational studies have focused exclusively on male subjects, it will be necessary to expand our understanding of these effects across sex. While no sex differences have been shown in the neuroimmune gene expression response to acute alcohol challenge as far as IL‐1β, TNF‐α, and IL‐6 in the hippocampus (Gano et al., ; Gano A, Mondello JE, Doremus‐Fitzwater TL, Deak T, manuscript in preparation), there are more notable differences that emerge as EtOH exposure becomes chronic. For instance, it has been shown that sex differences in the neuroimmune responses to chronic EtOH may be particular to the phase of intoxication (specifically emerging in withdrawal) and would therefore be ideally suited to examination using this novel approach (Alfonso‐Loaches et al., ; Hashimoto and Wiren, ; Wilhelm et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that while acute EtOH challenge results in a robust release of CORT, chronic EtOH engenders a blunted CORT response to future challenges (Spencer and McEwen, ). The hippocampus was selected as the target brain area of interest due both to prior data having shown its sensitivity to the cytokine‐inducing effects of EtOH (Gano et al., ,b), as well as its vulnerability to the effects of adolescent alcohol exposure (Risher et al., ). In the first experiment, a dose–response approach was used to analyze cytokine concentrations following either a saline injection, or an intraperitoneal (i.p.)…”
mentioning
confidence: 99%